From values to action: the role of personal and social values in shaping K−12 teachers' wellbeing and professional outcomes - Hessa Al-Thani; Malavika E. Santhosh; Mashael Al-Dosari (Frontiers in Education)
IntroductionTeachers' personal and social values are key determinants of their goals, behaviors, and interactions within the school environment. This systematic review explores the values upheld by K−12 teachers, examining their impact on teachers' wellbeing and their professional outcomes. Anchored in Schwartz's theory of human values, this study investigates the close and complex relationships between teachers' core values—namely, conservation, openness to change, self-transcendence, and self-enhancement—and their subsequent influence on wellbeing and professional outcomes.MethodsEmploying the PRISMA methodology, this review identifies, screens, and shortlists relevant articles, ultimately selecting 15 research articles for inclusion.ResultsThe analysis reveals the prevalence of 10 essential human values held by teachers, with benevolence being the most extensively examined value (n = 15), followed by achievement values (n = 12). These values shape salient aspects of teachers' professional lives, encompassing their wellbeing, instructional effectiveness, classroom management abilities, work engagement, job satisfaction, and self-efficacy. Specifically, teaching effectiveness (n = 5) and classroom management skills (n = 3) were found to be the most influenced by these core values.DiscussionThis research provides valuable insights for policymakers and educational leaders, offering a framework for fostering environments that help teachers cultivate values conducive to their wellbeing and professional success. The results serve as a guide for the development of policies and educational strategies that aim to enhance teacher satisfaction, promote teaching self-efficacy, and optimize classroom management practices.